Metastatic basal cell skin cancer with distant metastatic skeletal lesions: a clinical case report - A. P. Polyakov; A. V. Buharov; D. A. Miroshnichenko (Опухоли головы и шеи)
Clinical cases of distant metastasis of basal cell skin cancer are extremely rarely described in the international publications. This is probably due to the specific locally advanced growth of this histological type of tumor, as well as to the improvement of radical treatment methods for this group of patients. However, despite the development of both diagnostic research methods and treatment tactics, a large number of patients, especially when the primary tumor is located on the face and neck region, choose less effective and not always radical methods of treatment. In turn, non-radical removal of the primary tumor leads not only to difficulties in local control of the disease, but also to lymphogenous, as well as hematogenous spread of tumor cells and the manifestation of systemic metastasis.In the article, we present a clinical case of metastatic basal cell skin carcinoma of the periorbital region with lesions of the bones of the skeleton, namely the thoracic vertebrae manifested 11 years after the detection of the primary tumor.